DEVELOPMENT OF STUDENTS' PROFESSIONAL COMPETENCES BASED ON ARTIFICIAL INTELLIGENCE (Universal International Scientific Journal, 2026)
This article analyzes the possibilities of using artificial intelligence (AI) technologies to improve the quality of professional training of students. Artificial intelligence plays an important role in individualizing the learning process, creating an adaptive learning environment, real-time analysis and assessment, as well as in the formation of practical skills. The article also examines the impact of AI-based learning platforms, virtual laboratories and simulations on the quality of education. Recommendations are made for the modernization of professional education using AI.
Keywords: Artificial intelligence, vocational training, adaptive learning, virtual laboratories, educational simulations, digital technologies, educational quality, individualized learning.